2012
DOI: 10.1080/15374416.2012.632346
|View full text |Cite
|
Sign up to set email alerts
|

Does Social Anxiety Predict Rumination and Co-Rumination Among Adolescents?

Abstract: Social anxiety in adolescence is manifested by anxiety about and avoidance of social interactions. The present study examined whether social anxiety predicts higher levels of both rumination and co-rumination over time. Rumination and co-rumination were studied as possible outcomes because the cognitive content of these processes often involves interpersonal concerns. A three-wave longitudinal study of 575 adolescents (aged 13-16 years old) was conducted over 6 months. Adolescent girls reported higher levels o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
58
2
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 62 publications
(75 citation statements)
references
References 29 publications
7
58
2
3
Order By: Relevance
“…Although previous research found that individuals who ruminate at high levels are more likely to engage in co-rumination with their best friend over time (Jose et al, 2012), it is possible that these findings were not replicated due to the design of the current study. Because Jose et al (2012) utilized a longitudinal design, it is reasonable to suggest that a one-shot design is not sufficient in capturing the temporal sequence of emotion regulation processes between rumination and corumination. It would be fruitful for future dyadic studies to employ a longitudinal design to examine the unfolding of this process over time.…”
Section: Discussioncontrasting
confidence: 51%
See 4 more Smart Citations
“…Although previous research found that individuals who ruminate at high levels are more likely to engage in co-rumination with their best friend over time (Jose et al, 2012), it is possible that these findings were not replicated due to the design of the current study. Because Jose et al (2012) utilized a longitudinal design, it is reasonable to suggest that a one-shot design is not sufficient in capturing the temporal sequence of emotion regulation processes between rumination and corumination. It would be fruitful for future dyadic studies to employ a longitudinal design to examine the unfolding of this process over time.…”
Section: Discussioncontrasting
confidence: 51%
“…shown that people who tend to ruminate are also more likely to co-ruminate with their friends (Jose, Wilkins, & Spendelow, 2012). Although rumination and co-rumination are very similar, scholars have examined rumination in comparison to co-rumination in order to substantiate that these two constructs are indeed different from one another (Calmes & Roberts, 2008;Stone et al, 2011;Jose et al, 2012).…”
Section: Rumination and Co-ruminationmentioning
confidence: 99%
See 3 more Smart Citations